The Effect of Interactive Multimedia on the Loud Reading Skills in English Subjects for the Child with Mental Disability on 7TH Grade of SLB Panca Bakti Mulia Surakarta in the Academic Year of 2018/2019 - Sinta Ayu Saputri (Indonesian Journal of Disability Studies, 2019)
Abstract This research aims to know the influence of interactive multimedia on the loud reading skills in english subjects for the child with mental retardation on 7TH grade of SLB Panca Bakti Mulia Surakarta in the academic year of 2018/2019. This research methods uses an experimental of single subject research with A-B-A design. A-B-A design have three phases, first is baseline 1 (A1), the intervention (B), and the last is baseline 2 (A2). The subject of this research is a child with mental retardation on 7TH grade of SLB Panca Bakti Mulia Surakarta in the academic year of 2018/2019. The technique of collecting data used an oral test to find out the loud reading skills of child. The technique of analysing data used descriptive statistical analysis with visual graphics. The result of this study shows the everage value of the subject's loud reading skills in the first baseline phase was 35.5 with a low category to increase in the intervention phase to 84.5 with a high category and in the second baseline phase becoming 90.9 with a high category. The result of the analysis showed an increase in the loud reading skills in each condition with fairly good stability. Based on the result, the conclusion of this research is interactive multimedia has an influence on the loud reading skills in english subjects for the child with mental retardation on 7TH grade of SLB Panca Bakti Mulia Surakarta in the academic year of 2018/2019.